Clinical association study on the matrix metalloproteinase expression in the serum of patients with connective tissue disease complicated with interstitial lung disease - Hong Chen*; Jun Tang*; Juhua Liang; Dan Huang; Chunfeng Pan; Sha Liu; Xiuri Du; Liju Tao (Archives of Rheumatology, 2023)
Objectives: This study was implemented to reveal the expression and the clinical correlation of matrix metalloproteinases (MPSs) with connective tissue disease (CTD) complicated with interstitial lung disease (ILD). Patients and methods: This clinical study was conducted with 260 patients (151 males, 109 females; mean age: 47.3±12.5 years; range, 29 to 67 years) between October 2019 and October 2020. Among the subjects, 100 were CTD patients (CTD group), 80 were CTD patients with ILD (CTD-ILD group) and 80 were healthy individuals (control group). The MMP-2, -3, -7, and -9 levels in the serum of the three groups were detected by enzyme-linked immunosorbent assay. Results: Serum levels of MMP-3, -7, and -9 in the CTD-ILD group were higher, while the MMP-2 level was lower than those in the CTD group and the control group. The MMP-7 level in the serum of the CTD-ILD group was positively related to C-reactive protein, erythrocyte sedimentation rate, and rheumatoid factor and negatively correlated with immunoglobulin G and complement 3. The MMP-7 expression in the serum was positively correlated with forced expiratory volume in one second (FEV1%), FEV1/forced expiratory volume (FVC), and FVC in CTD-ILD patients. Pearson statistical analysis revealed that there was a significant positive correlation between the MMP-7 expression and the percentage of B cells in the serum of CTD-ILD patients. Conclusion: Expressions of MMP-3, -7, and -9 are significantly increased in the serum of patients with CTD and related interstitial lung lesions, and the high expression of MMP-7 indicates dynamic lung lesions, which is possible to be used as a possible biomarker for early diagnosis and assessment of disease progression.